2014
DOI: 10.1007/s00775-014-1124-7
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoazurin from Sinorhizobium meliloti as an electron donor to copper-containing nitrite reductase: influence of the redox partner on the reduction potentials of the enzyme copper centers

Abstract: Pseudoazurin (Paz) is the physiological electron donor to copper-containing nitrite reductase (Nir), which catalyzes the reduction of NO2 (-) to NO. The Nir reaction mechanism involves the reduction of the type 1 (T1) copper electron transfer center by the external physiological electron donor, intramolecular electron transfer from the T1 copper center to the T2 copper center, and nitrite reduction at the type 2 (T2) copper catalytic center. We report the cloning, expression, and characterization of Paz from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Its extinction coefficient was determined to be 3.58 Ϯ 0.09 mM Ϫ1 · cm Ϫ1 at 595 nm and pH 7.0 when completely oxidized, which is similar to that of Paz from P. pantotrophus (41). The determination of copper showed that 1 mM protein contained 0.88 Ϯ 0.12 mM copper atoms, indicating that per mol bound recombinant Paz, there was 1 mol Cu, which is in agreement with previous reports (42)(43)(44)(45).…”
Section: Resultssupporting
confidence: 89%
“…Its extinction coefficient was determined to be 3.58 Ϯ 0.09 mM Ϫ1 · cm Ϫ1 at 595 nm and pH 7.0 when completely oxidized, which is similar to that of Paz from P. pantotrophus (41). The determination of copper showed that 1 mM protein contained 0.88 Ϯ 0.12 mM copper atoms, indicating that per mol bound recombinant Paz, there was 1 mol Cu, which is in agreement with previous reports (42)(43)(44)(45).…”
Section: Resultssupporting
confidence: 89%
“…SmNir was identified to be a pseudoazurin (SmPaz) containing only a type 1 copper center [21]. Catalytic activity of Nir is maximal at pH ~ 5-6 and drops rapidly at higher pH, which is accompanied with a decrease in T1-T2 electron transfer rate [10,[22][23][24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These studies also showed that though the T2 site is distorted at pH ~ 8, the metal center retains the capability of binding nitrite, suggesting that the lack of activity at high pH is not associated with substrate binding. Furthermore, the reduction potentials measured for most as-purified Nirs are against a favorable T1→T2 electron transfer reaction, which led to hypothesize that they are modulated upon interaction with nitrite and the physiological donor to favor electron transfer [21,[25][26][27]. This means that a decrease in potential should cautiously be taken as the possible cause of catalytic activity loss at high pH and that other factors such as the pH-dependent topological characteristics of the Cys-His bridge should also be taken into consideration.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations